2015 European Control Conference (ECC) 2015
DOI: 10.1109/ecc.2015.7330547
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of threshold models for collective actions in social networks

Abstract: In this paper, we study the asymptotic behaviors of threshold models used to describe the formation of collective actions in social networks. At each time instant, each agent of the network makes a choice between two possible actions. The decision is made on the basis of the actions chosen by its neighbors and the value of a dynamically updated threshold. The main novelty of the proposed model is the introduction of a parameter accounting for the level of self-confidence of the agents, which affects the dynami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 16 publications
1
10
0
Order By: Relevance
“…A wide variety of collective limiting behaviors is observed and its relationship with the self-confidence parameter and the chosen decision mechanism is highlighted. A preliminary version of this work has been presented in [28]. This paper extends previous results to the case of star and ring graphs.…”
Section: Introductionsupporting
confidence: 68%
See 4 more Smart Citations
“…A wide variety of collective limiting behaviors is observed and its relationship with the self-confidence parameter and the chosen decision mechanism is highlighted. A preliminary version of this work has been presented in [28]. This paper extends previous results to the case of star and ring graphs.…”
Section: Introductionsupporting
confidence: 68%
“…Corollary 6. System (5), (6), with F and G given by (28) and (29), respectively, and initial condition (8) As for the complete graph, also for the star graph it can be observed that the WAL scenario shows a wider variety of asymptotic behaviors with respect to the UAL scenario. In particular, in the latter the initial activity pattern a(0) is never maintained indefinitely and the persistent oscillations for β < 1 occur only under the singular condition τ = µ(β) (while in the WAL scenario they show up for the entire range of τ values).…”
Section: B Uniform Activity Levelmentioning
confidence: 99%
See 3 more Smart Citations